An Exploration of The Social Conditions of Communities Around Disposal Sites (Case Study of Ganet Landfill, Tanjungpinang City) - Vitasari; Ismail, Khodijah; Raza'i, Tengku Said (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2024)
This research uses a descriptive qualitative method to explain the social conditions of the people living around the Ganet Landfill. The focus of the discussion is mainly on the environmental, health and comfort aspects of the community affected by the presence of the landfill. The main objective of this research is to understand how the social life of the community is formed as a result of the landfill. The results show that the environmental conditions, especially groundwater, meet the physical requirements. On the public health aspect, especially related to ARI disease, is the most dominant. On the aspect of comfort, the community felt the odor that sometimes appeared, most of them did not feel the nuisance of flies. Although accustomed and adapted to the existence of the landfill, the community still expects improved waste management at the Ganet landfill. This hope aims to improve the quality of the environment, public health, and the comfort of living in the area. The conclusion of this study provides a holistic picture of the social impact of the landfill on the community, highlighting their challenges and expectations related to the conditions surrounding the Ganet landfill.